Theoretical study of Captopril Derivatives as a possible drugs by using Quantum mechanics methods (Journal of the College of Basic Education, 2024)
The project concern with using of Quantum mechanics Calculation methods Semi – empirical (AM1, PM3 ) methods by using the program Hyper chem. 8.08 to calculate the equilibrium geometrical structure of the drugs. Captopril and it's derivatives (R= -NH2, -O, -CL, -S, -OH)Which are yet unused as a drugs .The physical properties of the drugs and it's derivatives Were calculate at their equilibrium geometrical structure as total energy entropy , free energy , heat capacity, dipole moment, EHOMO, ELOMO, Electronic energy, Nuclear energy, Ionization energy, Electron affinity and the IR, UV-Vis spectra . The theoretical results showed that energy of the derivatives ( - OH, - O) Were similar to that of the drug and both have an ionization energy similar to that the drug, this result was improved by the similar polarity of the drug and derivatives.